Persepsi Guru Kelas Terhadap Penerapan Model Student Team Achievement Division pada Pelajaran Sains di Kelas IV Sekolah Dasar - M Marjohan; Yulia Nurlita Sari (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2016)
This study aims to provide an overview of the perceptions of fourth grade teachers on the application of the STAD Model in Science lessons at the elementary school 47 of Jambi city. This research is a qualitative descriptive study. The informants of this study were class teachers, principals and IV elementary school students. Data collection techniques used were observation, interviews, and documentation. Data analysis uses steps of data reduction, data display, and conclusion. The results of this study can be concluded that in implementing the STAD model the teacher performs the material presentation phase, group work, individual tests, individual development score calculations, team awards and in preparing the STAD model by preparing activity sheets and answer sheets, assigning groups, presenting material , doing group activities, evaluating, rewarding group achievements, recalculating the group's initial score. As for the obstacles faced, lack of student interest, insufficient class hours, constraints in the division of groups and students are not familiar with the STAD model.